Market level innovations to improve vegetable intake in urban areas in Nigeria - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
Pilot results have been disseminated. For both interventions, there are signs of uptake based on anecdotal evidence from the field. For example, in Lagos and Ife, 6-8 weeks post-intervention most participating street food vendors were still offering the vegetable option and the idea had spread to other vendors.